2007
DOI: 10.1345/aph.1e466
|View full text |Cite
|
Sign up to set email alerts
|

Obesity: Implementation of a Weight Management Pharmaceutical Care Service

Abstract: The Auburn University Pharmaceutical Care Center's Healthy Habits program has been successful in helping patients decrease total body weight, BMI, and risk of weight-related complications. In addition, the program has increased the opportunity to identify other pharmaceutical care needs of patients and help establish the role of pharmacists in the management of obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 9 publications
1
42
0
Order By: Relevance
“…In 2007, a survey of 6000 people was conducted in six European countries, including the UK [17] . This survey showed that 64% of the population sample identified ‘community‐pharmacy‐based services’ as an alternative to clinic services.…”
Section: Discussionmentioning
confidence: 99%
“…In 2007, a survey of 6000 people was conducted in six European countries, including the UK [17] . This survey showed that 64% of the population sample identified ‘community‐pharmacy‐based services’ as an alternative to clinic services.…”
Section: Discussionmentioning
confidence: 99%
“…Another example is the weight management service provided in a single pharmaceutical care centre on a college campus in the United States of America (USA) between 1996 and 2006 [14]. The intervention consisted of an initial consultation with the pharmacist, with fortnightly follow-ups until target weight was reached, with 3-monthly reviews.…”
Section: Weight Management In the Community Pharmacymentioning
confidence: 99%
“…A further study conducted in a single, university campus pharmaceutical care centre in the USA assessing the effectiveness of pharmacist education and counselling (and in some cases counselling plus pharmacotherapy) produced mean weight loss of 3.6 kg. 19 …”
Section: Introductionmentioning
confidence: 99%